ASSOCIATION OF RISK FACTORS OF CEREBRAL PALSY – A MATCHED CASE CONTROL STUDY (International Journal of Physiotherapy, 2020)
Background: Cerebral palsy (CP) is one of the leading causes of childhood disability worldwide. The exact etiology of CP is poorly understood, but many risk factors are related to problems during pregnancy, labor, and delivery. The age and sex-matched control study were done to evaluate the association of perinatal risk factors with the development of CP among children in a rural area.Methods: The study was conducted in the Division of Physical Medicine and Rehabilitation (PMR). Seventy clinically diagnosed CP children as cases and 70 children without CP as controls were included. Information regarding perinatal risk factors was collected from the parents of the children. Data were collected and statistically analyzed by using the Mc-Nemar chi-square test.Results: The study results suggested that children with male sex (53%) had a higher incidence of CP compared to female (47%) children. Spastic diplegia (60%) was the most common subtype of CP. The significant ‘p’ value (< 0.01) reveals that all the perinatal risk factors are associated with the development of CP.Conclusion: This study concluded that spastic diplegia was the most common subtype of CP. The perinatal riskfactors such as preterm, low birth weight, birth asphyxia, and neonatal seizures had a significant association with the development of CP.